Calcium-Sensing Receptor Contributes to Hyperoxia Effects on Human Fetal Airway Smooth Muscle - Roesler, Anne M.; Ravix, Jovanka; Bartman, Colleen M.; Patel, Brijeshkumar S.; Schiliro, Marta; Roos, Benjamin; Nesbitt, Lisa; Pabelick, Christina M.; Martin, Richard J.; MacFarlane, Peter M.; Prakash, Y. S. (Frontiers in Physiology, 2021)
Supplemental O2 (hyperoxia), necessary for maintenance of oxygenation in premature infants, contributes to neonatal and pediatric airway diseases including asthma. Airway smooth muscle (ASM) is a key resident cell type, responding to hyperoxia with increased contractility and remodeling (proliferation, extracellular matrix (ECM) production), making the mechanisms underlying hyperoxia effects on ASM significant. Recognizing that fetal lungs experience a higher extracellular Ca2+ ([Ca2+]o) environment, we previously reported that the calcium sensing receptor (CaSR) is expressed and functional in human fetal ASM (fASM). In this study, using fASM cells from 18-22 week human fetal lungs, we tested the hypothesis that CaSR contributes to hyperoxia effects on developing ASM. Moderate hyperoxia (50% O2) increased fASM CaSR expression. Fluorescence [Ca2+]i imaging showed hyperoxia increased [Ca2+]i responses to histamine that was more sensitive to altered [Ca2+]o, and promoted IP3 induced intracellular Ca2+ release and store-operated Ca2+ entry: effects blunted by the calcilytic NPS2143. Hyperoxia did not significantly increase mitochondrial calcium which was regulated by CaSR irrespective of oxygen levels. Separately, fASM cell proliferation and ECM deposition (collagens but not fibronectin) showed sensitivity to [Ca2+]o that was enhanced by hyperoxia, but blunted by NPS2143. Effects of hyperoxia involved p42/44 ERK via CaSR and HIF1α. These results demonstrate functional CaSR in developing ASM that contributes to hyperoxia-induced contractility and remodeling that may be relevant to perinatal airway disease.